Effects of in situ exopolysaccharide production and fermentation conditions on physicochemical, microbiological, textural and microstructural properties of Turkish-type fermented sausage (sucuk) - Dertli, Enes; Yilmaz, Mustafa Tahsin; Tatlisu, Nevruz Berna; Toker, Omer Said; Cankurt, Hasan; Sagdic, Osman (ELSEVIER SCI LTD, 2016)
In this work, the role of in situ exopolysaccharide (EPS) production under different fermentation conditions on physicochemical, microbiological, textural and microstructural properties of sucuk was determined. For this purpose, the effect of EPS producing strains (control, strain 1, strain 2 and mixture) and fermentation conditions (fermentation temperature; 14, 16 and 18 C and time; 8, 12 and 16 days) on physicochemical, microbiological, textural and microstructural properties were investigated using response surface methodology. In situ EPS production was observed to remarkably affect these properties while fermentation conditions were also seen to dominantly influence the physicochemical properties of sucuk, revealing that the ripening temperature appeared to be more determinant factor. EPS producing cultures enhanced the textural properties of sucuk which became harder, less adhesive and tougher. The microstructural analysis revealed the formation of web -like structure by in situ EPS production in sucuk mix during fermentation process. This study revealed the importance of in situ EPS production on final technological properties of sucuk. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Sucuk; Exopolysaccharides; Texture; Microstructure; LACTIC-ACID BACTERIA; QUALITY CHARACTERISTICS; STARTER CULTURES; MEAT-PRODUCTS; STYLE SAUSAGE; COLOR; FAT; ATTRIBUTES; YOGURT; Food Science & Technology